A haven for her heart - Mason, Susan Anne (Mason, Susan Anne. Redemption's light, 2020)
Toronto, 1939. Released after being incarcerated in a woman's reformatory for being pregnant and unmarried, Olivia Rosetti's family is unwilling to forgive her. She ends up homeless. Well-to-do widow Ruth Bennington hires Olivia to help with a maternity home for troubled women, and for years Olivia focuses herself on the home. Greek widower Darius Reed is determined to protect his daughter from the prejudice that killed his wife. When his employer orders him to buy the property the maternity home is on, he is attracted to Olivia. Can love prove stronger than the secrets and hurts of the past? -- adapted from back cover